Mechanism of shear transformation in Ge-Bi-Te alloys - Sun, Chang Woo; Lee, Jeong Yong; Kim, Yong Tae (WILEY-V C H VERLAG GMBH, 2009)
Since the rhombohedral unit cell in the NaCl lattice is caused by distortion along the < 111 > NaCl direction, the same phenomenon is expected during phase transition of Ge-Bi-Te (GBT). With this assumption, we performed transmission electron microscopy (TEM) studies on the phase transition in GBT alloys annealed at temperatures between the two crystallization temperatures. Atomic-scale TEM images show the formation of a GBT intermediate structure during the phase transition. Using the obtained results, we developed a new phase transition model in which the Ge/Bi layers are ordered in the < 111 > direction; further, continuous shearing and dilation occur in the {111} plane in < 111 > direction. (C) 2009 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim
Keywords: PHASE-CHANGE MATERIALS; SYSTEM; NACL